Treatment options in Cheyne-Stokes respiration - Winfried J. Randerath (Therapeutic Advances in Respiratory Disease, 2010)
About half of the patients suffering from heart failure present with sleep-disordered breathing. In most cases obstructive and central breathing disturbances (including Cheyne-Stokes respiration [CSR]) coexist. CSR is defined by a waxing and waning pattern of the tidal volume. While its pathophysiology has not been elucidated completely, increased ventilatory sensitivity for CO 2 and therefore an imbalance of the respiratory drive and effort, a chronic hyperventilatory state, and changes of the apnoeic threshold are considered to play a relevant role. However, CSR in heart failure impairs survival and quality of life of the patients and is therefore a major challenge of respiratory sleep medicine. If CSR persists despite optimal medical and interventional therapy of the underlying cardiac disorder, oxygen supply, continuous positive airway pressure (CPAP), and bilevel pressure are often trialled. However, there is insufficient evidence to recommend oxygen or bilevel treatment. CPAP has proven to improve left ventricular function. In addition, retrospective analyses suggested a reduction of mortality under CPAP in heart failure patients with CSR. However, these findings could not be reproduced in the prospective controlled CanPAP trial. More recently, adaptive servoventilation (ASV) has been introduced for treatment of CSR or coexisting sleep-related breathing disorders. ASV devices aim at counterbalancing the ventilatory overshoot and undershoot by applying variable pressure support with higher tidal volume (TV) during hypoventilation and reduced TV during hyperventilation. ASV has proven to be superior to CPAP but the long-term efficacy and the influences on cardiac parameters and survival are still under investigation.